Challenges and Strategies For Effective Resource Utilization In Secondary Schools - Syafaruddin Syafaruddin; Amiruddin Amiruddin; Andi Ibbar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This research investigates the prevalent challenges and identifies strategic approaches for effective resource utilization in secondary schools. Through a mixed-methods study involving quantitative analysis and qualitative interviews, the research highlights significant problems such as budget constraints, outdated educational materials, and disparities in resource distribution between urban and rural schools. The study reveals that 75% of surveyed schools encounter difficulties in resource allocation, with urban schools having better access to technology and trained personnel compared to their rural counterparts. Qualitative findings underscore the importance of several strategies to optimize resource usage. Needs-based allocation is identified as a critical approach, with schools that tailor resources to specific needs reporting improvements in student engagement and achievement. The integration of technology, combined with comprehensive teacher training on digital tools, is pivotal in enhancing learning experiences. Moreover, collaboration with the community and local businesses emerges as a valuable source of additional resources and real-world learning opportunities. The establishment of resource-sharing networks among schools is also noted as an effective measure to mitigate the impact of budget constraints and promote a more equitable distribution of materials and expertise. This study contributes to the discourse on educational equity and efficiency, offering actionable insights for policymakers, educators, and administrators. By emphasizing the need for localized solutions, technological equity, and community engagement, the research points towards a more equitable and efficient educational landscape. Future research directions include exploring the longitudinal impacts of these strategies on educational outcomes and the role of policy reforms in supporting resource optimization efforts.